(untitled) (Ibrahim Cardiac Medical Journal, 2024)
Background & objective: Stroke is a leading cause of death and a serious disability for adults. However, it is preventable and manageable, provided a complete updated profile (incidence, prevalence, and long-term outcome) of the disease is in our hands. The present study was therefore undertaken to assess the demographic, clinical characteristics, and outcome of the stroke patients admitted to the Dhaka Medical College Hospital. Methods: This descriptive cross-sectional study was conducted in the Department of Medicine, over a period of 12 months between January 2004 and December 2004 at the Dhaka Medical College Hospital (DMCH), Dhaka. The study sample consisted of 101 stroke patients who were admitted to the Green Medicine Unit of DMCH. However, stroke patients who were too severely debilitated or in a state of stupor were not allowed to participate in the study. Through pertinent clinical laboratory and imaging tests, stroke risk variables were evaluated. The outcome was evaluated in terms of the number of patients cured, died, or remained static. Result: There was no significant difference between ischemic and haemorrhagic stroke patients in terms of age (p = 0.658), sex (p = 0.276) and diurnal variation of its occurrence (p = 0.490). While diabetes mellitus and ischaemnic heart diseases were generally associated with haemorrhagic stroke (p = 0.039 and p = 0.056 respectively), hypertension was more or less common in ischemic stroke (p = 0.176). In both groups, hemiplegia was the most frequent cause of admission, after coma. While seizures were more common in the ischemia group, vomiting was a more common manifestation in the hemorrhagic group. The majority of patients in both groups maintained a steady pulse and normal blood pressure. The total cholesterol level was relatively greater in the ischemic group than in the hemorrhagic group. The mean HDL level in the hemorrhagic group was significantly higher than in the ischemic cohort. However, there was no appreciable difference in serum LDL and Tg levels across the groups. A substantial proportion of patients in both groups had to stay in the hospital for a brief period (10 or < 10 days). After receiving treatment, nearly 85% of the patients in the hemorrhagic group and 76.3% of the patients in the ischemic group were cured; some 5.5% in the ischemic group and 4.3% in the haemorrhagic group died of the disease. Conclusion: The study concluded that smoking, uncontrolled hypertension, and diabetes mellitus are the three main risk factors for stroke. After a median treatment of 7 days, most patients in both the hemorrhagic and ischemic groups recovered, leaving a few to die of the disease. The risk of stroke can significantly be reduced by lowering blood pressure, treating diabetes, and giving up smoking. Ibrahim Card Med J 2023; 13 (1&2): 47-52